(untitled) (Journal of Economic Research & Business Administration, 2016)
The article discusses the question on evaluation of the effectiveness of the personnel management system operation, within a context of the appli-cation of information technologies. The evaluation of the effectiveness of personal management is a relevant objective that requires a joint efforts of all business leaders to resolve the issue of personnel management system development, this requires an open communication platform for interac-tion, survey, data collection. As part of the task the analysis of personnel evalu-ation methods was conducted, so as to form a complex model of optimized methods in the form of a knowledge base. Consolidation of methods, analysis instru- ments and measurements, in one information-analytical platform, allows to form analytics of state of development of human resource management in terms of types of companies/branches/regions, what enables company executives to understand the structure of the turn-over, the structure of the personnel management system program to identify «narrow spaces», to promote the formation of employee engagement programs in the growth of company efficiency. Architecture platform is suggested as integrations of portals, which are oriented on human resource management particular tasks, as: «Career and Youth» Portal, «Human Resources assessment» (in the form of online-service), analytical portal on recruitment condition in region/country, information portal devoted to HR-questions.